Recent entomological enquiry on mosquito fauna in Circeo National Park - Claudio De Liberato; Adele Magliano; Flavia Farina; Luciano Toma (Istituto Superiore di Sanità, 2015)
The present study was carried out in Circeo National Park (Lazio region, Central Italy), in order to collect data about mosquito (Diptera, Culicidae) fauna in a protected area for biodiversity. From 2003 to 2004 seasonal surveys allowed to collect and to identify 380 larvae and 713 adult mosquitoes in 6 sites. A total of 15 mosquito species belonging to 6 genera were recorded; the most abundant species were Culex pipens Linnaeus, 1758 known as the main West Nile virus vector, Ochlerotatus detritus (Haliday, 1933) and Culiseta annulata (Dhrank, 1776). Present data show a noteworthy number of other mosquito species, even if less abundant, reflecting the considerable environmental richness. Respect to the past collections of Anophelinae mosquitoes carried out in the same area once affected by malaria, the present research represents the first monitoring of the whole Culicidae Family in Circeo National Park, up to now. This paper reports the collected data as a first base for a future checklist in this protected area.